2021
DOI: 10.1002/adfm.202100969
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐Coated 10B Carbon Dots for Precise Boron Neutron Capture Therapy in a Mouse Model of Glioma In Situ

Abstract: Novel boron‐containing carbon dots (BCDs) are designed and prepared for boron neutron capture therapy (BNCT) with superior water solubility and excellent optical property for tracking 10B in vitro and in vivo. Encapsulation of BCDs using exosomes (Exos) from macrophages yields BCD–Exos of ≈100 nm. Fluorescent imaging shows that the BCD–Exos are internalized and distributed around the nuclei of U‐87‐MG glioma cells. BCD–Exos are also verified to cross the blood–brain barrier and significant accumulation in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…In another study by Qiao et al, the authors developed the CDs modified with d-glucose and l-aspartic for targeting brain tumor cells (C6 cells) [336]. Recently, Li et al prepared exosome-coated 10 B-CDs for BNCT of brain tumors, which was demonstrated on a glioma mice model [337]. The excellent accumulation of these CDs in the brain glioma in vivo allowed an effective BNCT, achieving a prolonged survival rate of mice compared to control samples (a survival ratio of 100% for 30 days in case of BNCT and a survival ratio of 0% after 15 days of experiments in case of control group, i.e.…”
Section: Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Qiao et al, the authors developed the CDs modified with d-glucose and l-aspartic for targeting brain tumor cells (C6 cells) [336]. Recently, Li et al prepared exosome-coated 10 B-CDs for BNCT of brain tumors, which was demonstrated on a glioma mice model [337]. The excellent accumulation of these CDs in the brain glioma in vivo allowed an effective BNCT, achieving a prolonged survival rate of mice compared to control samples (a survival ratio of 100% for 30 days in case of BNCT and a survival ratio of 0% after 15 days of experiments in case of control group, i.e.…”
Section: Cdsmentioning
confidence: 99%
“…The excellent accumulation of these CDs in the brain glioma in vivo allowed an effective BNCT, achieving a prolonged survival rate of mice compared to control samples (a survival ratio of 100% for 30 days in case of BNCT and a survival ratio of 0% after 15 days of experiments in case of control group, i.e. mice without therapy) [337].…”
Section: Cdsmentioning
confidence: 99%
“…Except the above strategy to achieve cancer therapy, there are still other advanced nanotechnology to be developed with CDs for diverse cancer. For example, boron neutron capture therapy (BNCT) was a noninvasive radiation therapeutic modality for cancer therapy and Li et al designed one kind of novel boron-containing carbon dots (BCDs) for the BNCT by tracking 10B in vitro and in vivo 234 . With the encapsulation of BCDs by exosomes (Exos), researchers designed the BCD-Exos which could internalize and distribute around the nuclei of U-87-MG glioma cells (Figure 20 A-B).…”
Section: Targeted Cancer Therapymentioning
confidence: 99%
“…(E) Gross images of mice brains and microscopic images of H&E-stained tumor sections in each group. Adapted with permission from 234 , copyright 2021 Wiley-VCH GmbH.…”
Section: Figurementioning
confidence: 99%
“…Li et al prepared boron CDs using boron phenylalanine (BPA) and glucose as precursors through hydrothermal heating and coating by exosomes to explore the activity of boron neutron capture therapy (BNCT) against glioma in mice. More importantly, these nanomaterials have shown a more excellent permeability across the BBB than the CDs alone (staying only up to 15 min), and then they shed from the brain [37]. Furthermore, their fluorescence imaging properties are adequate for precisely identifying glioma, which qualifies these materials as "promising theranostics".…”
Section: Exosomesmentioning
confidence: 99%